Rates of Serious Infections in HIV‐Infected Patients Receiving Tumor Necrosis Factor Inhibitor Therapy for Concomitant Autoimmune Diseases. Issue 3 (March 2017) - Wangsiricharoen, Sintawat; Ligon, Colin; Gedmintas, Lydia; Dehrab, Admad; Tungsiripat, Marisa; Bingham, Clifton; Lozada, Carlos; Calabrese, Leonard
Abstract : Objective: To estimate the incidence of serious infections in patients with HIV infection and autoimmune disease who were treated with tumor necrosis factor (TNF) inhibitors, and to compare these rates by stratified viral load levels. Methods: Using a unified search strategy, 4 centers identified HIV‐infected patients exposed to TNF inhibitors. Patient characteristics and infection data were assessed via chart review in all patients who were ≥18 years old and who received TNF inhibitor therapy after HIV diagnosis, between January 1999 and March 2015. Results: We studied 23 patients with 26 uses of TNF inhibitor therapy (86.7 person‐years of followup). Two (8.7%) experienced at least 1 serious infection episode, for an overall incidence rate of 2.55 per 100 patient‐years (95% confidence interval [95% CI] 0.28–9.23). The incidence rate per 100 patient‐years was 3.28 (95% CI 0.04–18.26) among patients with a viral load >500 copies/ml at therapy initiation and 2.09 (0.03–11.65) among patients with a viral load ≤500 copies/ml. Conclusion: This study suggests that the rate of serious infections in patients with HIV infection under active care who have received treatment with TNF inhibitors may be comparable to the rates observed in registry databases.